Meta Analisis : Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, Leverage, Terhadap Earnings Management - Khomara, Rania; Wuga, Silviana; Handayani, Maria Vania; Meiden, Carmel (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study aims to integrate the effect of firm size, leverage, and institutional ownership on earnings management. Supervision of agents is carried out through a governance mechanism so that the actions of agents are in line with the principal's objectives. The research method used is a meta-analysis study. Earnings management journal articles publications are searched using the PoP application with a period limit of 2017-2022. A total of 30 samples of articles used purposive sampling method with a total of 200 data samples for 5 years. The results of the integration obtained in this study are firm size, institutional ownership, and leverage have a positive effect on the practice of Earnings Management